2013
DOI: 10.7860/jcdr/2013/7718.3777
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Erectile Dysfunction as Assessed by IIEF-5 in North Indian Type 2 Diabetic Males and Its Correlation with Variables

Abstract: Introduction: The aim of this study was to assess the severity of the erectile (ED) dysfunction among type 2 diabetic men. For subjective information patients were asked to fill up the IIEF questionnaire. This study was also done to correlate ED with other variables like age, obesity, duration of diabetes, degree of diabetic control and complications of diabetes. Neuropathy was assessed objectively by using the Vibration Perception Threshold (VPT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
2
15
2
Order By: Relevance
“…The current study showed that IIEF score declines with longer duration of diabetes and poorer glycaemic control using the questions directed to evaluate the erectile function, similar results reported by a study conducted by AlMogbel et.al 26 and agreed by the work published by Goyal et al, [27,28] .…”
Section: Discussionsupporting
confidence: 90%
“…The current study showed that IIEF score declines with longer duration of diabetes and poorer glycaemic control using the questions directed to evaluate the erectile function, similar results reported by a study conducted by AlMogbel et.al 26 and agreed by the work published by Goyal et al, [27,28] .…”
Section: Discussionsupporting
confidence: 90%
“…increase from 0.4%(20-30 years) to 0.5%(41-50 years), 1.3% (51-60years) and to 9.6% in those who were aged 71-80 years (4). Another study conducted in Italy increase age was found to increase the odds of ED (15).…”
Section: Discussionmentioning
confidence: 88%
“…Another crosssectional cohort study done in Tehran, Iran reported that the prevalence of erectile dysfunction among DM patients is 18.8% (10). Another study done in North India the occurrence of erectile dysfunction among type 2 DM patients is 77.2% (4). A cross-sectional study conducted among 200 DM patients in Iran the prevalence of erectile dysfunction is 82.5% (N=200 Men=100 and Women=100) (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of ED in South Asian patients with diabetes has been reported to be between 38-97% (Table 6) [115][116][117][118][119][120][121]. The main factors associated with ED are age, duration of diabetes, glycemic control, presence of neuropathy and retinopathy.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%